INFLUENCE OF K, S AND ZN ON GROWTH, YIELD, NUTRIENT UPTAKE AND QUALITY PARAMETERS OF MUSTARD IN UDIC HAPLUSTEPTS KANPUR - AND D. D.TIWARI, SOM RAJ (The Bioscan, 2018)
The Present investigation were conducted for two rabi season during 2011-12 and 2012-13 in the field of Nawabganj Research Farm, C.S. Azad University of Agriculture and Technology, Kanpur, to study the effect of potassium, sulphur and zinc application on yield attributes, yield, quality parameters of mustard.Treatment consisted of 3 levels each of potassium, ( 0, 60 and 80 kg/ ha ), sulphur ( 0, 40 and 60 kg /ha) and zinc (0, 3.0 and 5.0 kg /ha). The Results indicated that yield attributes,seed and Stover yield increased significantly with the use of K,S and Zn over the control.K, S and Zn application @ 60 kg K2O/ha, 40 kg S /ha and 3.0 kg Zn / hasignificantly increased yield attributes, seed and stover yields and further increase, levels of these nutrients, reduced yield attributes, seed and stover yield of mustard during both the years. The uptake of nutrients significantly increased upto K60 S40 Zn3.0 levels and further increasing of K, S and Zn doses, decline nutrients uptake by mustard crop (vari. Pitambri).Oil and protein content significantly increased by the use of 60 kg K2 O and 40 kg S /ha.